Transport of p-nitrophenyl-alpha-maltoside by the maltose transport system of Escherichia coli and its subsequent hydrolysis by a cytoplasmic alpha-maltosidase. - Reyes, M (1986)
In wild-type Escherichia coli the activity of the maltose transport system is dependent on a periplasmic maltose-binding protein. It has been possible, however, to isolate mutants in which transport activity is mediated by the membrane components of the system and is no longer dependent on the periplasmic binding protein. In this manuscript we show that in these binding protein-independent strains, p-nitrophenyl-alpha-maltoside is a potent inhibitor of maltose transport. In contrast, p-nitrophenyl-alpha-maltoside is only a weak inhibitor of maltose transport in wild-type bacteria. In addition, we show that p-nitrophenyl-alpha-maltoside is transported by the binding protein-independent strains but not by wild-type bacteria. We were able to detect transport of this compound because there is a cytoplasmic enzyme that cleaves p-nitrophenyl-alpha-maltoside. This enzyme has not previously been described. We show that although the synthesis of this enzyme is subject to the same regulation as the components of the maltose regulon, and is MalT dependent, it is not coded for by a known mal gene. We refer to this enzyme as alpha-maltosidase. These results strengthen our proposal that the membrane components of the maltose transport system comprise a recognition site for maltose and related substrates.